Alice's adventures in wonderland & Through the looking-glass - Carroll, Lewis 1832-1898; Tenniel, John Sir 1820-1914 (Mumbai Wilco Pulishing House, 2006)
A little girl finds adventure down a rabbit hole and through a mirror.
Alice's adventures in Wonderland -- Through the looking-glass.
"Complete & unabridged."--Cover.
Includes bibliographical references.
Keywords: Alice (Fictitious character : Carroll) -- Fiction; English fiction -- 20th century; Fantasy literature, English; Alice (Fictitious character : Carroll) -- Fiction; Fantasy; Fantasy fiction